2018
DOI: 10.3390/jcm7120525
|View full text |Cite
|
Sign up to set email alerts
|

Personality and the Moderating Effect of Mood on a Verbal Aggressiveness Risk Factor from Work Activities

Abstract: One of the trends in the current research in psychology is to explore how personal variables can determine a person’s communication style. Our objective was to find out the moderating effect of mood in the relationship between the five big personality traits and an aggressive verbal communication style risk factor from work activities in a sample of nursing professionals. This study is a quantitative descriptive design. The final sample was 596 nurses with an age range of 22 to 56 years. An ad hoc questionnair… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Despite some criticism on the empirical studies on job crafting, blamed as a neoliberal response to the increased job insecurity and loss of meaning at work, the current research on collaborative job crafting highlights the relevance of proactive behaviors in all professional fields. It has been understood as potentially beneficial both for employees and organizations [48], not only in industrial settings but also in the educational [49]. Thus, interventions should be developed to improve teachers' well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some criticism on the empirical studies on job crafting, blamed as a neoliberal response to the increased job insecurity and loss of meaning at work, the current research on collaborative job crafting highlights the relevance of proactive behaviors in all professional fields. It has been understood as potentially beneficial both for employees and organizations [48], not only in industrial settings but also in the educational [49]. Thus, interventions should be developed to improve teachers' well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of empirical studies on job crafting among union representatives, recent trends in work and organizational psychology highlighted the relevance of proactive behaviors in all the professional fields. They have been gradually considered as potentially beneficial both for employees and organizations (Molero Jurado et al 2018), not only in industrial settings but also in educational (Cansino et al 2018) or environmental fields (Junquera and Barba-Sánchez 2018). It seems that the concept of understanding the trade union organizations as entities that defend workers' health and rights has ignored the fact that situations like burnout might also occur within these organizations (Cho and Kim 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This relationship has been confirmed by several empirical studies. For example, it has been demonstrated that high levels of "Neuroticism" in maladapted subjects with high negative affect 40 and high levels of burnout in healthcare personnel 41 predict the use of aggressive, hostile and authoritarian language, [42][43][44] while the rest of personality traits are more associated with prosocial behaviour. [45][46][47][48][49][50] Another factor which influences the communication pattern of healthcare professionals is the presence of negative emotions.…”
Section: Communication Styles In Healthcare Professionalsmentioning
confidence: 99%
“…The items are answered on a Likert-type scale where one is equivalent to "strongly disagree" and five to "strongly agree". However, Items 9, 10, 15,19,21,26,27,29,31,37,40,43,45,47,49,56,58,60,62,65,68, 69, 72, 90, 91, 93, 96 must be inverted for proper correction and analysis. In the original version of the instrument, the authors reported reliability levels for the scales that varied from 0.82 to 0.88 in the general population and from 0.83 to 0.87 in a sample of students.…”
Section: Instrumentsmentioning
confidence: 99%